Diterpenoid phytoalexin factor, a bHLH transcription factor, plays a central role in the biosynthesis of diterpenoid phytoalexins in rice. (7th December 2015) - Yamamura, Chihiro; Mizutani, Emi; Okada, Kazunori; Nakagawa, Hitoshi; Fukushima, Setsuko; Tanaka, Atsunori; Maeda, Satoru; Kamakura, Takashi; Yamane, Hisakazu; Takatsuji, Hiroshi; Mori, Masaki
Summary: Rice ( Oryza sativa ) produces diterpenoid phytoalexins (DPs), momilactones and phytocassanes as major phytoalexins. Accumulation of DPs is induced in rice by blast fungus infection, copper chloride or UV light. Here, we describe a rice transcription factor named diterpenoid phytoalexin factor (DPF), which is a basic helix‐loop‐helix (bHLH) transcription factor. The gene encoding DPF is expressed mainly in roots and panicles, and is inducible in leaves by blast infection, copper chloride or UV. Expression of all DP biosynthetic genes and accumulation of momilactones and phytocassanes were remarkably increased and decreased in DPF over‐expressing and DPF knockdown rice, respectively. These results clearly demonstrated that DPF positively regulates DP accumulation via transcriptional regulation of DP biosynthetic genes, and plays a central role in the biosynthesis of DPs in rice. Furthermore, DPF activated the promoters of COPALYL DIPHOSPHATE SYNTHASE2 ( CPS2 ) and CYTOCHROME P450 MONOOXYGENASE 99A2 ( CYP99A2 ), whose products are implicated in the biosynthesis of phytocassanes and momilactones, respectively. Mutations in the N‐boxes in the CPS2 upstream region, to which several animal bHLH transcription factors bind, decreased CPS2 transcription, indicating that DPF positively regulates CPS2 transcription through the N‐boxes. In addition, DPF partly regulates CYP99A2 through the N‐box. This study demonstrates that DPF acts as a master transcription factor in DP biosynthesis. Significance Statement: Phytoalexins are generally produced in response to pathogen infections, but sometimes accumulate in certain tissues in the absence of pathogens. Here we characterize a transcription factor that coordinates expression of phytoalexin biosynthetic genes in rice, in both developmental and abiotic and biotic stress contexts.